2004
DOI: 10.1016/j.physletb.2004.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Charm quark–antiquark correlations in photon–proton scattering

Abstract: Correlation of charm quark -charm antiquark in γp scattering are calculated in the k t -factorization approach. We apply different unintegrated gluon distributions (uGDF) used in the literature. The results of our calculations are compared with very recent experimental results from the FOCUS collaboration. The CCFM uGDF developed recently by Kwieciński et al. gives a good description of the data. New observables are suggested for future studies. Predictions and perspectives for the HERA energies are presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…These grids are then used via a two-dimensional interpolation in the spaces (x 1 , k 2 1,t ) and (x 2 , k 2 2,t ) associated with each of the two incoming partons. The Kwieciński unintegrated parton distributions were used recently in applications to cc photoproduction [35], cc correlations in nucleon-nucleon collisions [25], production of gauge bosons [36], production of Standard Model Higgs boson [37], inclusive production of pions [38], production of direct photons [39]. Good agreement with experimental data was obtained in the case when the data exist.…”
Section: B Unintegrated Gluon Distributionsmentioning
confidence: 93%
“…These grids are then used via a two-dimensional interpolation in the spaces (x 1 , k 2 1,t ) and (x 2 , k 2 2,t ) associated with each of the two incoming partons. The Kwieciński unintegrated parton distributions were used recently in applications to cc photoproduction [35], cc correlations in nucleon-nucleon collisions [25], production of gauge bosons [36], production of Standard Model Higgs boson [37], inclusive production of pions [38], production of direct photons [39]. Good agreement with experimental data was obtained in the case when the data exist.…”
Section: B Unintegrated Gluon Distributionsmentioning
confidence: 93%
“…It was demonstrated [11,22,23] that the leading-order off-shell matrix elements of the photon-gluon fusion |M| 2 (γg * → cc) combined with the noncollinear evolution of gluon densities in a proton A(x, k 2 T , µ 2 ) effectively simulate contribution from the charmed quark excitation subprocess cg → cg. Next, some c −c correlations in high energy γp scattering have been studied [24] and comparisons to the recently measured data of the FOCUS collaboration at Fermilab were made. In particular, it was shown that the analysis of the kinematical correlations of charmed quarks opens new possibilities for verifying models of non-collinear gluon evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Here the Feynman diagrams are calculated taking into account the virtualities and all possible polarizations of the incident partons. There are widely discussed applications of the k ⊥ -factorization approach to hard QCD processes like the J/ψ hadroproduction [6], charmonium production [7], heavy quark photo- [8,9] and hadroproduction [10], Higgs boson production [11,12]. Some exclusive processes in the framework of the k ⊥ -factorization approach are described in detail in [13].…”
Section: Introductionmentioning
confidence: 99%